2018
DOI: 10.5154/r.rchscfa.2017.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Una metodología para la caracterización del uso del suelo mediante imágenes de media resolución espacial

Abstract: Introducción: La caracterización de los usos del suelo representa uno de los insumos indispensables para el manejo de los recursos naturales a diferentes escalas.Objetivo: Desarrollar una metodología para caracterizar el uso del suelo en la cuenca superior del arroyo del Azul (Buenos Aires, Argentina), a través de la fusión de imágenes satelitales de media resolución espacial.Materiales y métodos: Se utilizó una serie temporal de 23 imágenes del índice de vegetación de diferencia normalizada (NDVI, por sus sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…Particularly a negative trend in carbon gains (annual productivity) and a positive trend in seasonality would be indicating serious effects on biodiversity at ecosystem scale and for the provision of several ecosystem services (Paruelo et al, 2016;Vitousek et al, 1997). Land cover changes or the intensification of productive practices seem to be the responsible for the changes mentioned, or they indicate different works carried out at a more detailed scale (Baldi et al, 2006;Guevara-Ochoa et al, 2018;Lara and Gandini, 2014;Vazquez and Zulaica, 2013). These processes reveal a strong component of human control on seasonal carbon dynamics and on ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly a negative trend in carbon gains (annual productivity) and a positive trend in seasonality would be indicating serious effects on biodiversity at ecosystem scale and for the provision of several ecosystem services (Paruelo et al, 2016;Vitousek et al, 1997). Land cover changes or the intensification of productive practices seem to be the responsible for the changes mentioned, or they indicate different works carried out at a more detailed scale (Baldi et al, 2006;Guevara-Ochoa et al, 2018;Lara and Gandini, 2014;Vazquez and Zulaica, 2013). These processes reveal a strong component of human control on seasonal carbon dynamics and on ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The upper creek basin of Del Azul has an area of 1024 km 2 , see (Guevara Ochoa et al, 2018), and the altitude of the basin varies between 367 and 129m.…”
Section: Hydrological Datamentioning
confidence: 99%
“…In addition, among many other spectral vegetation indices, the NDVI has been proved to effectively detect seasonal and inter-annual changes in vegetation growth and activity, particularly at low or moderate vegetation amounts such as in grassland areas [41,42]; however, it tends to saturate under high biomass conditions and is very sensitive to canopy background variation [41]. In spite of its limitations, previous studies across the RPG region have shown that monthly NDVI time series data effectively discriminate temperate grasslands from other cover types (e.g., croplands, forested areas) based on their unique phenological characteristics [16,24,40,43,44]. It was therefore preferred in this scenario to other available spectral indices.…”
Section: Land Cover Characterizationmentioning
confidence: 99%
“…For each period, the NDVI datasets were stacked and resampled to 30 m pixel size using the nearest neighbor method in order to preserve the original image radiometric information. Given that ground-truth information was not available for annual periods prior to 2014, unsupervised classifications were performed to each annual NDVI dataset using the ISODATA algorithm (following a similar approach that was previously performed for the RPG region; see [16,43]. The ISODATA algorithm was set to generate a maximum of 20 classes using 100 iterations, a tolerance threshold of 5%, and maximum standard deviation of 1.…”
Section: Land Cover Characterizationmentioning
confidence: 99%